PENGEMBANGAN SISTEM INFORMASI GEOGRAFISPEMETAAN ZONA BANJIR DI KOTA PALEMBANGBERBASIS ANNDROID - Ali Ibrahim; Musdiono - (Universitas Sriwijaya, 2016)
AbstractGovernment institutions Public Works has a function to cope with flooding. In the flood of data management using a computer-based system. Location data flood managed manually. With this problem researchers will produce a solution to make flood mapping. The goal is to provide effectiveness and efficiency in the management of data and information to make the handling of the flood area. Making information systems researchers waterfall method and Mapbox. The results of this study are science and technology mapping flood zones with android.Keywords: Geographic Information System, Mapping Flood Zone, Mapbox, androidÂ AbstrakLembaga pemerintah Pekerjaan Umum memiliki fungsi untuk mengatasi banjir. Dalam pengelolaan data banjir menggunakan sistem berbasis komputer. Data lokasi banjir dikelola secara manual. Dengan masalah tersebut peneliti akan menghasilkan solusi untuk membuat pemetaan banjir. Tujuannya memberikan efektifitas dan efisiensi dalam pengelolaan data dan informasi untuk melakukan penanganan wilayah banjir. Pembuatan sistem informasi peneliti menggunakan metode waterfall dan Mapbox. Hasil penelitian ini adalah IPTEK pemetaan zona banjir dengan android.Kata kunci : Sistem Informasi Geografis, Pemetaan Zona Banjir, Mapbox, androidÂ Â